Accuracy investigation of 3D printed PLA with various process parameters and different colors - Hanon, Muammel M.; Zsidai, László; Ma, Quanjin (Elsevier Ltd, 2021)
The accuracy of three-dimensional (3D) printing is how the dimensions of a measured product are close to its original model's nominal values. Thus, dimensional accuracy is essential for determining the machine's reliability to produce each object according to the expected results. In this study, the influence of 3D printing process parameters on the dimensional accuracy of specimens manufactured using Polylactic acid (PLA) material is investigated. Based on fused deposition modeling (FDM) technology, cylindrical and dog-bone tensile test samples are fabricated at various process parameters, including build orientation, raster direction angle, and layer thickness. PLA filaments with three different colors (white, grey, and black) are utilized to produce the required test pieces. The dimensional accuracy for cylindrical (diameter and length) and dog-bone (width and thickness) samples have been evaluated. The nominal values are considered the reference to determine the accuracy percentage for each specimen. The weight of all test pieces is also examined, and its precision is assessed. The optimum process parameter settings have been defined to minimize the error percentage in the dimensions of the printed parts. According to the results, a high overall dimensional accuracy of 98.81% was achieved, which indicates the ability of commercial FDM 3D printers as an inexpensive and decent quality alternative for producing utilitarian parts. The filament's color displayed a notable impact on the test pieces' weight, where the difference between the heaviest (white) and lightest (black) specimens is almost a percentage of 7.24%. A remarkable influence was noticed for the layer thickness parameter on the accuracy, meanwhile the raster direction angle parameter appeared no effect when the number of layers and the contour size are the same. The data obtained from this study might help identify the optimum configurations that guide the production of components using thermoplastic filaments through FDM 3D printing.